Organocomplexos de zinco contendo anti-inflamatório não esteroides e diiminas aromáticas planas: novos fármacos potenciais - Schiavenin, Ariane (My University, 2020)
Strategies have been developing to obtain new medicines. Bioisosterism represents an approach used by the medicinal chemist for the rational modification of lead compounds into safer and more clinically effective agents. Evidently, the synthesis of organocomplexes has been an important strategy in the planning of new drugs with examples of great improvements in therapeutic efficacy. Thus, this work aimed at the synthesis of new zinc complexes with nonsteroidal anti-inflammatory drugs (NSAIDs), as well as the chemical characterization and the previous toxicity by cytotoxicity, and evaluating the ability of these compounds to interact with DNA. As a result, four new zinc II ternary complexes containing the NSAIDs diclofenac (Diclof) and ibuprofen (Ibup) and zinc neutral linker were obtained by the two-step solvent metalligand complexation method (1. Zn-Ibup-Bipy, 2. Zn-Ibup-Phen, 3. Zn-Diclof-Bipy, 4. Zn-Diclof-Phen). Molecular structures were determined by NMR, FTIR and HR-MS which demonstrated that complexes are binuclear systems of general formula [Zn(RCOO?)2N-binder]. In silico studies were performed to toxicity and physicochemical properties and biological target prediction. Cytotoxic was determined by MTT assay. Results indicated a relative absence of toxicity to these organometallic zinc derivatives. It is also observed that compound Zn-Diclof-Bipy and Zn-Diclof-Phen showed high potential to be submitted to studies of evaluation of biological activity, without potential theoretical toxic effects. Plasmidial DNA breakdown capacities were evaluated by producing single and double breaks (DNA FII and FIII) from plasmid incubation with complex solutions in the concentration range 0 to 400 ?mol·L?1 in experiments with the presence and absence of light. Both experiments did not show significant differences (P ? 0.05) in induced DNA cleavage activity between the maximum study concentrations (400 ?mol·L?1) and the negative controls for both complexes. The types of complex 1 and 2 interactions with the secondary DNA structure were determined by titrating a CT-DNA solution with complex solutions and monitored by circular dichroism spectrometry. Complex 1 was not cytotoxic at the concentrations tested against the Vero cell line. The results showed that both complexes interact with the grooves of the secondary structure of CT-DNA by electrostatic attraction, but without evidence of alteration in the primary structure. Thus, four new compounds were synthesized, characterized and had their previous toxicities determined. These compounds are promising new drugs, with the next step being evaluations of their activity [resumo fornecido pelo autor].
Estratégias vêm sendo desenvolvidas para obtenção de novos medicamentos. O bioisosterismo representa uma abordagem usada pela química medicinal para a modificação racional de compostos em agentes mais seguros e clinicamente eficazes. Evidentemente, a síntese de organocomplexos representa uma estratégia importante no planejamento de novos fármacos com exemplos de grandes melhorias na eficácia terapêutica. Assim, este trabalho teve como objetivos a síntese de novos complexos de zinco ligados a anti-inflamatórios não esteroideis (AINEs), bem como a caracterização química e a avaliação da toxicidade prévia por citotoxicidade, além de avaliar a capacidade desses compostos em interagir com o DNA. Como resultado, quatro novos complexos ternários de zinco II contendo os AINEs diclofenaco (Diclof) e ibuprofeno (Ibup) e ligados ao íon zinco foram obtidos pelo método de complexação de metaligante de solvente em duas etapas (1. Zn-Ibup-Bipy, 2. Zn- Ibup-Phen, 3. Zn-Diclof-Bipy, 4. Zn-Diclof-Phen). As estruturas moleculares foram determinadas por NMR, FTIR e HR-MS as quais demonstraram que os complexos são sistemas binucleares de fórmula geral [Zn (RCOO?) 2N-binder]. Foram realizados estudos in silico de toxicidade, propriedades físico-químicas e predição de alvos biológicos. A citotoxicidade foi determinada pelo ensaio MTT. Os resultados indicaram uma relativa ausência de toxicidade para esses organometálicos derivados de zinco. Observa-se também que os compostos Zn-Diclof-Bipy e Zn-Diclof-Phen apresentam alto potencial para serem submetidos a estudos de avaliação da atividade biológica, sem potenciais efeitos tóxicos teóricos. As capacidades de degradação do DNA de Plasmidial foram avaliadas pela produção de quebras simples e duplas (DNA FII e FIII) a partir da incubação de plasmídeos com soluções complexas na faixa de concentração de 0 a 400 ?mol·L ? 1 em experimentos com a presença e ausência de luz. Ambos os experimentos não mostraram diferenças significativas (P ? 0,05) na atividade de clivagem de DNA induzida entre as concentrações máximas de estudo (400 ?mol·L ? 1) e os controles negativos para ambos os complexos. Os tipos de interação do complexo 1 e 2 com a estrutura secundária do DNA foram determinados pela titulação de uma solução de CT-DNA com soluções complexas e monitorados por espectrometria de dicroísmo circular. O complexo 1 não foi citotóxico nas concentrações testadas contra a linha celular Vero. Os resultados mostraram que ambos os complexos interagem com os sulcos da estrutura secundária do CT-DNA por atração eletrostática, mas sem evidências de alteração na estrutura primária. Assim, quatro novos compostos foram sintetizados, caracterizados e tiveram sua toxicidade prévia determinadas. Esses compostos são drogas promissoras potenciais [resumo fornecido pelo autor].
Keywords: Química farmacêutica; Elementos químicos; Agentes anti-inflamatórios não esteróides; Zinco; Pharmaceutical chemistry; Chemical elements; Non-steroidal anti-inflammatory agents; Zinc